The Influence of Quality of Service, Accessibility, Transparency, Speed, and Communication on the Performance of Employees at the Lawang Kidul Subdistrict Office in Muara Enim Regency - Erlatifah, Erlatifah; Hamid , Abdul; Ilpiyanto , Marko (Utami Publisher, 2026)
The purpose of this study is to determine and analyze the influence of service quality, accessibility, transparency, speed, and communication, individually and collectively, on employee performance at the Lawang Kidul Sub-district Office in Muara Enim Regency. The research method used in this study was quantitative, using a questionnaire distributed to respondents. Data quality was tested using validity, reliability, and normality tests. The analysis used descriptive and inferential analyses using statistical calculations using multiple regression formulas, partial and simultaneous tests, and the coefficient of determination. The analysis results obtained that service quality has a significant effect on employee performance at the Lawang Kidul District Office, Muara Enim Regency. Accessibility does not have a significant effect on employee performance at the Lawang Kidul District Office, Muara Enim Regency. Transparency has a significant effect on employee performance at the Lawang Kidul District Office, Muara Enim Regency. Speed has a significant effect on employee performance at the Lawang Kidul District Office, Muara Enim Regency. Communication has a significant effect on employee performance at the Lawang Kidul District Office, Muara Enim Regency. Service quality, accessibility, transparency, speed and communication have a significant effect together on employee performance at the Lawang Kidul District Office, Muara Enim Regency.